UPAYA UNIT PELAKSANA TEKNIS (UPT) PENGELOLAAN SAMPAH DALAM PENANGANAN SAMPAH DI KELURAHAN PEMATANG PUDU KECAMATAN MANDAU TAHUN 2017 - Rafhichoh "; M.Y.Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Waste management is the collection, transportation, processing recycling or disposal of garbage material. Produced from human activities and it is asually managed to reduce its impact on environmental health and aesthetics. All the efforts of the waste management has been carried out by Technical Implementation Unit (UPT) for Waste Management that handles all about garbage problems and Pematang Pudu garbage bank institution as well. The formulation of the problem in this study is How is the effort of the Technical Implementation Unit (UPT) of waste management in the area of Pematang Pudu sub-district Mandau in 2017? And the aim of this studys is to know how is the effort of the Technical Implementation Unit (UPT) of Waste Management in the area of Pematang Pudu sub-district Mandau in 2017. To know the factors that influenced the efforts of Technical Implementatiton unit of Waste Management in the area of Pematang Pudu sub-district Mandau. This research uses descriptive qualitative approach. The results of this research is the lack of the waste management handling from the stakeholders, the lack of facilities and infrastructures such as garbage transportation garbage can and the only one land fill. And the lack of our citizen participation in reducing and managing the waste. Keywords: Waste Management, Technical Implementation Unit (UPT) for Waste Management, Garbage Bank